Cyclonic storms of the Arabian Sea, 1877-1980 - MOOLEY, D. A.; MOHILE, C. M. (MAUSAM, 1984)
The series of cyclonic storms/severe cyclonic storms forming over the Arabian Sea and reaching the sections of the coast around it during the period 1877- 1980 are studied, Although the annual series of storms reaching the coast around the Arabian Sea is homogeneous that of the storms forming over the Arabian Sea shows significant increase duping the period 1965 -80. Increase in the number of storms during 1965 -80 may be due to better aids for detection of storms or due to more favourable conditions for formation of storms. Some climatological features about the storms reaching the west coast of India are also presented. Poisson probability model is a good fit to the number of: storms forming over the sea and to the number of storms reaching the coast around the Arabian Sea during the year and this model has been used to estimate the frequencies of storms reaching the coast during the next 50-yeap period.